Radiation dosimetry of [131I]ICF01012 in rabbits: Application to targeted radionuclide therapy for human melanoma treatment. Issue 11 (24th September 2018) - Jouberton, Elodie; Perrot, Yann; Dirat, Béatrice; Billoux, Tommy; Auzeloux, Philippe; Cachin, Florent; Chezal, Jean‐Michel; Filaire, Marc; Labarre, Pierre; Miot‐Noirault, Elisabeth; Millardet, Corinne; Valla, Clémence; et al.
Abstract : Purpose: Dosimetry for melanoma‐targeted radionuclide therapy (TRT) with [ 131 I]ICF01012, a melanin ligand, has been previously evaluated in mice bearing melanomas. In this study, activity distribution and dosimetry are performed on healthy rabbits (Fauve de Bourgogne) using SPECT‐CT imaging and ex vivo measurements. Material and Methods: Ex vivo biodistribution (i.v. injection: 370 kBq/kg, n = 2 per point) is performed on blood, eyes, brain, lung, liver, kidneys, heart, stomach, and spleen. Dosimetry calculations follow the MIRD formalism: S values are calculated from CT images using the GATE Monte Carlo platform and activity distributions are obtained from SPECT‐CT imaging (i.v. injection: 37 MBq/kg n = 3 per point). A specific study is presented to assess dose to human retina. Results: Time‐integrated activities based on SPECT‐CT are in accordance with ex vivo measurements except for spleen. Doses to liver and eyes are the most significant, with respectively, 6.38 ± 0.50 Gy/GBq (evaluated through SPECT‐CT imaging) and 45.8 ± 7.9 Gy/GBq (evaluated through ex vivo measurements). Characterization of ocular [ 131 I]ICF01012 biodistribution in rabbits and quantification of melanin allowed to assess a dose of 3.07 ± 0.70 Gy/GBq to human retina. Conclusion: This study sustains [ 131 I]ICF01012 as a good candidate for melanoma TRT and open perspectives for personalized dosimetry calculation during phase I clinical transfer.